2000
DOI: 10.1080/004982500237631
|View full text |Cite
|
Sign up to set email alerts
|

In vitro inhibition of human P450 enzymes by prenylated flavonoids from hops, Humulus lupulus

Abstract: 1. Several unique flavonoid compounds have recently been isolated from hops, Humulus lupulus, and their presence has been detected in beer. Their chemical structures are similar to other plant-derived compounds, many present in the human diet, that have been shown to have cancer chemopreventive properties due, in part, to inhibition of cytochrome P450 enzymes that activate carcinogens. Additionally, preliminary studies have shown these flavonoids (at 100 microM) to be inhibitory of P450-mediated activation rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
112
0
9

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(124 citation statements)
references
References 25 publications
3
112
0
9
Order By: Relevance
“…They have been considered inert and non-essential for human health; however, in the last few years it has been shown that £avonoids a¡ect a wide variety of biological systems in mammals, exhibiting antioxidant, anti-in£ammatory, antiviral, antiproliferative, and anticarcinogenic e¡ects [1]. Studies show that several £avonoids can inhibit or activate the cytochrome P450 (CYP) enzyme system in vitro and in vivo [2,3]. Recently in animal studies much attention has been paid to the antioxidant properties and the inhibitory role of £avo-noids in various stages of tumor development.…”
Section: Introductionmentioning
confidence: 99%
“…They have been considered inert and non-essential for human health; however, in the last few years it has been shown that £avonoids a¡ect a wide variety of biological systems in mammals, exhibiting antioxidant, anti-in£ammatory, antiviral, antiproliferative, and anticarcinogenic e¡ects [1]. Studies show that several £avonoids can inhibit or activate the cytochrome P450 (CYP) enzyme system in vitro and in vivo [2,3]. Recently in animal studies much attention has been paid to the antioxidant properties and the inhibitory role of £avo-noids in various stages of tumor development.…”
Section: Introductionmentioning
confidence: 99%
“…Xanthohumol and other prenylated chalcones are now attracting greater attention in the medical field. To date, some prenylflavonoids examined in vitro present many biological activities: inhibition of the growth of breast cancer (MCF-7) cells in a dose-dependent manner (Miranda et al, 1999); inhibition of the cytochrome P450-mediated activation of procarcinogens (Henderson et al, 1998); inducing the activity of the carcinogen-detoxifying enzyme, quinone reductase (Miranda et al, 2000). Other biological activities include inhibition of bone resorption, inhibition of diacylglycerol acyltransferase and antimicrobial activities (Tobe et al, 1997;Tabata et al, 1997;Mizobuchi and Sato, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Compound 3, also known as dehydrocycloxanthohumol, is a pyranochalcone that has also exhibited a variety of biological activities. Compound 3 possesses anti-fungal, anti-proliferative, antimutagenic and antioxidative activities (Miranda et al, 1999;Gerhauser et al, 2002;Henderson et al, 2000;Miranda et al, 2000a;Miranda et al, 2000b;Stevens et al, 2003;Nikolic et al, 2005). Based upon the previous reports, both Compounds 1 and 3 seem to have similar activities against cancer cell behavior in vitro except anti-invasive effect.…”
Section: Discussionmentioning
confidence: 99%